Evaluation of recurrence and postoperative pain in laparoscopic inguinal hernia repair with mesh fixation verses without mesh fixation - Prasad, Dinesh; Khedkar, Indira; Modi, Mitesh (International Surgery Journal, 2018)
Background: Inguinal hernia affects both men and women but is much more common in men who comprise over 90% of operated patients. The purpose of this study was to determine whether elimination of tacking the mesh during endoscopic inguinal hernia repair results in decreased postoperative pain or complications, or both, without increasing the incidence of hernia recurrence. Methods: Patients age between 18 to 70 yrs, willing for laparoscopic surgery, suitable for elective laparoscopic surgery were included in the study. TEP or TAPP endoscopic inguinal hernia repairs would be performed with the patient under general anesthesia. Data collection have done by using a structured pre-prepared case performa. The patient evaluated both by radiological and laboratory investigations both pre-operatively and post-operatively. Results: There is no major significant difference in pain at 1 month after operation in both the group. Recurrence was higher among patient having mesh fixation and it was not statistically significant. Wound infection was occurring more among without fixation group and it was not statistically significant. Urinary retention was reported more among without fixation group and it was not statistically significant. Conclusions: Thus, it was concluded that there is no significant difference in recurrence rate in the both study group either with fixation or without fixation. There is no significant difference in pain at one month in the both study group either with fixation or without fixation. There is more pain (visual analogue scale more than two) at three months after operation in fixation group as compared to without fixation group. There is also high cost in fixation group as compared to without fixation group.